A Case Report Documenting a Rare Diagnosis of a Plasmablastic Lymphoma Situated Within Gingival Tissue in a Patient on Long‐Term Immunosuppressants for Kidney Transplant. Issue 2 (1st May 2014) - Darcey, James C.; Hall, Gillian; Roberts, Anthony
Abstract : Introduction: Plasmablastic lymphoma is a high‐grade life‐threatening immunologic malignancy most often found in patients with human immunodeficiency virus (HIV). It is regarded as a unique AIDS‐related lymphoma that has been described in individuals without HIV. Intraoral presentation in such circumstances is extremely rare. Case Presentation: A patient presented with an innocuous epulis and chronic periodontitis. The patient had a history of renal transplant and long‐term immunosuppression with cyclosporine. The localized area of gingival enlargement, although provisionally diagnosed as gingival disease modified by medication, was excised and subsequently confirmed as an acute plasmablastic lymphoma. Excised tissue was sent off for routine histopathologic examination. Latent membrane proteins were found for Epstein‐Barr virus. Atypical lymphoid tissue with multiple immune markers was indicative of a plasmablastic plasmacytoma, but this diagnosis was modified in light of the history of immunosuppression and positive Epstein‐Barr markers to a post‐transplant plasmablastic lymphoma. The patient was managed with a combination of chemotherapy and radiotherapy. The patient is now posttreatment, and there are no signs of recurrence or metastasis. Conclusions: This is a rare presentation. To our knowledge, there have been <10 oral cases ever reported in individuals without HIV. However, surgeons should recognize the importance of clinical diagnoses being supported with histopathologic examination to ensure that potentially life‐threatening misdiagnoses are not made.